Corrosion behavior of T24, T92, VM12, and AISI 304 steels exposed to KCl–NaCl–K2SO4–Na2SO4 salt mixtures. Issue 5 (8th December 2020) - Abu‐Warda, Najib; López, Antonio J.; Pedraza, Fernando; Utrilla, Maria V.
Abstract: The corrosion mechanisms of T24, T92, VM12, and AISI 304 steels are studied under the influence of NaCl–KCl, NaCl–Na2 SO4, and KCl–K2 SO4 salt mixtures in a dry air atmosphere at 650°C for 15 days. NaCl–KCl was the most aggressive deposit and AISI 304 stainless steel exhibited the highest corrosion resistance. There was no relation between the Cr content of the ferritic steels and their corrosion resistance in NaCl–KCl. In contrast, the resistance of high‐Cr steels was better when exposed to NaCl–Na2 SO4 and KCl–K2 SO4 . The high‐Cr and the low‐Cr steels were more susceptible to NaCl–Na2 SO4 and to KCl–K2 SO4, respectively. Abstract : The corrosion mechanisms of T24, T92, VM12, and AISI 304 steels are studied under the influence of NaCl–KCl, NaCl–Na2 SO4, and KCl–K2 SO4 salt mixtures in a dry air atmosphere at 650°C for 15 days. NaCl–KCl was the most aggressive deposit and AISI 304 stainless steel exhibited the highest corrosion resistance. There was no relation between the Cr content of the ferritic steels and their corrosion resistance in NaCl–KCl